Promoting deep learning in mathematics through conceptual exercises - Törnquist, Asger (Improving University Science Teaching and Learning, 2023)
We investigate the effects of posing non-traditional “conceptual” problems to university mathematics students as a means of promoting a deeper level of learning among a class of second year undergraduate mathematics students at the University of Copenhagen.